Developing Products for The Wat Sai Rama 3 Community with The Concept of Creating Uniqueness and Using Local Ingredients - Kiatkamonmarn, Chayawat; Tadawattanawit, Surakiat (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2026)
This research aims to 1) develop products for the Wat Sai Rama 3 community using the concept of creating uniqueness and utilizing local raw materials, and 2) study consumer satisfaction towards new products from the Wat Sai Rama 3 community developed with the concept of creating uniqueness and using local raw materials. The sample group consists of 62 customers who came to purchase community products. The study found that: 1) In terms of product development for the Wat Sai Rama 3 community, the research team elevated the community’s products by using the distinctive TONSAI brand that reflects the community’s identity, along with developing new products that showcase the culture and use local raw materials, such as Orange Peel Pia (Chinese pastry), reflecting Thai-Chinese way of life, and various flavored tarts, filled with giant lime/Bengal currants, adding value from local ingredients. 2) Regarding consumer satisfaction towards new products from the Wat Sai Rama 3 community developed with the concept of creating uniqueness and using local raw materials, it was found that overall, consumers had the highest level of satisfaction ( = 4.44), with the highest satisfaction in product and community uniqueness ( = 4.53), followed by price ( = 4.47). This reflects the success of the product development concept. Orange Peel Pia received higher satisfaction ( = 4.47), particularly in terms of product ( = 4.58), while Multi-Flavored Tarts ( = 4.36) stood out in terms of price ( = 4.46), indicating the success of both products in meeting consumer needs. The study results, showing high customer satisfaction in product and community uniqueness, reflect the effectiveness of the research’s approach in adding value under the concept of creating uniqueness and using local raw materials.